2000
DOI: 10.1073/pnas.050580497
|View full text |Cite
|
Sign up to set email alerts
|

Selective interaction between leptin and insulin signaling pathways in a hepatic cell line

Abstract: Leptin is a 16-kDa hormone secreted by adipocytes and plays an important role in control of feeding behavior and energy expenditure. In obesity, circulating levels of leptin and insulin are high because of the presence of increased body fat mass and insulin resistance. Recent reports have suggested that leptin can act through some of the components of the insulin signaling cascade, such as insulin receptor substrates (IRS-1 and IRS-2), phosphatidylinositol 3-kinase (PI 3-kinase), and mitogen-activated protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(154 citation statements)
references
References 53 publications
9
139
0
4
Order By: Relevance
“…Although many effects of leptin are mediated through the central nervous system (for PI3K-mediated effects of leptin on the brain refer to review; Plum et al 2005), this peptide can regulate metabolism through a direct action on tissues, such as pancreas and liver. In agreement with this finding, previous studies have shown that leptin activates PI3K in b-cells and hepatocytes , Harvey et al 2000, Szanto & Kahn 2000. Moreover, in primary rat hepatocytes, leptin induces PI3K-dependent activation of phosphodiesterase 3B, a cAMP-degrading enzyme, to suppress glucagon-induced cAMP elevation (Zhao et al 2000).…”
Section: Pi3k-mediated Effects Of Leptinsupporting
confidence: 76%
“…Although many effects of leptin are mediated through the central nervous system (for PI3K-mediated effects of leptin on the brain refer to review; Plum et al 2005), this peptide can regulate metabolism through a direct action on tissues, such as pancreas and liver. In agreement with this finding, previous studies have shown that leptin activates PI3K in b-cells and hepatocytes , Harvey et al 2000, Szanto & Kahn 2000. Moreover, in primary rat hepatocytes, leptin induces PI3K-dependent activation of phosphodiesterase 3B, a cAMP-degrading enzyme, to suppress glucagon-induced cAMP elevation (Zhao et al 2000).…”
Section: Pi3k-mediated Effects Of Leptinsupporting
confidence: 76%
“…1E), reflecting the lack of activation of JAK-2 by leptin in these animals. 20,22,24 When phosphorylated at a Ser residue by the protein kinase B or Akt kinase, FoxO1 is inactivated and migrates from the nucleus to the cytosolic compartment. 25 Thus the excess nuclear activity of FoxO1 in the livers of fructose-fed animals is again related to a deficit in the leptin-signal pathway through JAK-2 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Mounting evidence shows that leptin can also regulate the metabolism of fat and glucose, including attenuation of insulin action and sensitivity in peripheral tissues [37], and that it can function through some of the components of the insulin signaling cascade, thereby modifying insulin-induced changes in gene expression [38]. Plasma leptin concentrations have been shown to be related to insulin sensitivity in diabetic subjects [39].…”
Section: Discussionmentioning
confidence: 99%